Six of one: The relationship between social dominance orientation and orientation to cyclists - Nadia Williams (Social Sciences and Humanities Open, 2023)
Cycling uptake in Ireland is very low, and communications related to cycling and cyclists is generally negative. The author hypothesised that Social Dominance Theory can be applied to understand this. A survey was designed and distributed which allowed respondents to complete the well-established Social Dominance Orientation scale, and a Cyclist Orientation scale designed by the author to test a respondent's orientation towards cycling and cyclists. Scores for both were converted to percent so as to compare like for like. A correlation was found between respondents' SDO score and CO score. This suggests that there is a relationship between Social Dominance Orientation and one's attitude to cyclists.